Rare earth elements (REE) in crude oil in the Lansing-Kansas City formations in central Kansas: potential indications about their sources, locally derived or long-distance derived - McIntire, Michael Christopher (Kansas State University, 2014)
There are some who hold the view that liquid hydrocarbons in the upper Paleozoic formations in Kansas are being locally derived. It has been the long held belief that the liquid hydrocarbons found in Kansas have come from distant sources in Oklahoma. To shed further light on this issue about the origin of hydrocarbons in the upper Paleozoic formations in Kansas, a study was conducted to analyze the geochemical characteristics of REE in Lansing-Kansas City oils that were collected from several locations in a small area within Rooks County, Kansas. The total REE contents in these oils ranges from about 3.1 ng (or 10-12 gram) per Liter of oil to about 131 ng per Liter of oil. The pattern of relative distribution of the REEs for each oil sample has been constructed from values that were obtained by dividing the individual REE concentrations of a given oil sample by the respective concentrations of the REEs in a standard or a reference sample (such as PAAS, a representation of average argillaceous sediments in the crust that is commonly used for the analyses of a variety of crust originated sedimentary products). A standard- normalized relative distribution pattern of an oil sample can reveal an important history of chemical evolution of the oil of interest. The PAAS-normalized patterns of relative distribution of the REEs in the Lansing-Kansas City oils from Rooks County, Kansas are significantly diverse. Although nearly all oil samples investigated in this study have varied degrees of light REE-enrichment across the REE series from La to Sm, they differed in their relative Ce abundances. Some samples have positive Ce anomalies; some have negative Ce anomalies, and some others with the absence of any Ce anomaly. The oils also differed in their PAAS-normalized relative distribution of the middle rare earth elements (MREEs), ranging from Sm to Tb. All oil samples were relatively enriched in the MREEs, but with varied degrees of enrichment from a prominent one to almost a barely noticeable one. The oils differed in their relative distributions of Eu, as some were with a positive Eu anomaly, some with a negative Eu anomaly, and some with the absence of any Eu anomaly. The trends of the heavy rare earth elements (HREEs) from Tb to Lu among the oils ranged from nearly flat for the most oils to a progressive depletion across the series for few samples. Furthermore, the oils were varied in having prominently anomalous relative distributions, in some cases with a positive anomaly and in others with negative anomaly, for such elements as Tb, Ho, and Tm (MM-JS-04, MM-MC-3A, and MM-MC-01). The anomalies for Tb, Ho, Tm are reflections of enzyme activity of source material during its primary (growth) environment. The metals are known to be preferentially located at the active sites of the enzymes. The oils not only differed significantly in their REE-geochemical characteristics, they also had a wide range of K/Rb weight ratios from about 877 to about 2000. These high values are typically the ones that can be assigned to organic materials, well exceeding the range of values that are associated with common silicate minerals and rocks, having an average value of 250-350ppm. Different zones in the Lansing-Kansas City formations also show distinct REE distribution patterns. There are four broadly classified distribution patterns. MREE enrichment can be observed in samples with production from the middle Lansing-Kansas City zones (G-I). In samples with comingling Lansing-Kansas City zones, amplification of anomalies from differing source materials can be observed. The diversity in the REE distribution patterns and K/Rb ratios in oils collected from central Kansas makes a strong argument against long distance transportation from a distant source in Oklahoma
Keywords: Lansing-Kansas City formations; Rare Earth Elements; REE; Petroleum geology; Geology (0372)